Factors influencing the effective leadership succession planning: Study on a Malaysian GLC - Shamsulkahar, Abdul Shukor; Suhaidah, Hussain (UMP Press, 2019)
The scope of this research paper is to study on the factors influencing effective Leadership Succession Planning (LSP) of one of the main Government Linked Companies (GLC). Background of the study provides an understanding on the external factors as well that have an influence on the topic of study, which covers among others, on the Malaysian economic policy itself. This study is aimed to study the current factors and the gap that is influencing the effectiveness of current LSP initiatives by a service oriented of Malaysian Government Linked Company, and to highlight some key critical factors as proposed in the literatures. Factors influencing the effectiveness of LSP are also subject on the ability of the leaders to adopt to external changes particularly in the era of borderless economic and faster rate of technology changes, and there are some differences from one organization to another, subject to the nature of the business and their stakeholders. However, there are some common important factors can be used as guidelines and practices particularly from the research literatures. Therefore, qualitative study was conducted to be carried out to fulfill the objectives and to answer the research questions. An interview with the Group Chief Executive Officer (CEO) of one GLC, who is the subject matter expert. The recording from the interview was transcribed and further analyzed using ATLAS.ti software. The findings evidence that there are current practice of leadership succession planning in the company, anyhow there is a gap between the aspirations of the Group CEO and the availability of C-level replacement from within, and between the reality and the theories. Results of the findings identify the outcomes that need to be taken into action for a more effective LSP program. In the future, similar research approach can be conducted to other GLCs in order to analyze the similarities and complimentary aspirations with regards to LSP.